Ground penetrating radar (GPR) in road pavement assessment - Costa, André (2010)
GPR involves the transmission of high-frequency electromagnetic radio pulses into the ground, and the measure of the time elapsed between transmission and reception by a surface radar antenna, after reflection in a buried discontinuity. In a enormous wide range of applications, it assumes a growing importance in road assessment, because enables precise and continuous pavement layer thickness evaluation at high-speed velocities and simultaneously, through analysis of variation of dielectric constant of the inspected materials, detection of zones related with striping or segregation of hot mix asphalt, as well of contrasts in moisture of granular materials. Through the lifetime of a pavement GPR can assure fundamental information: in the aim of quality control or assurance of new pavements; monitoring during service time; or as inspection method to define rehabilitation strategies. Assume interest in network management, pavement design, monitoring and forensic disputes. The work carried out by the authors, confirms the potentialities of this method, and emphasizes integration of GPR data with video images and geographical positioning by GPS, as with other road pavement data, and deals with data acquisition and processing; as well statistical synthesis and interpretation; integration of GPR with data from other methods; and data report. The applied GPR method requires horn air launched antennas, and compares amplitude reflection in pavement surface with the amplitude reflection in a metallic plate to calculate dielectric values of the first layers. As an example of GPR inspection, it is presented 32 km of a left lane highway in both ways, inspected along three different lines (left and right wheels and centre line), in about 4 hours of field work, during daylight period and without traffic impact.